Pain Experiences and Their Relation to Opioid Misuse Risk and Emotion Dysregulation - Jonathan W. Nauser; Cecelia I. Nelson; Richard T. Gross; Alison M. Vargovich (Pain Research and Management)
Pain is a complex, multidimensional experience but often is measured as a unidimensional experience. This study aimed to separately assess the sensory and affective components of pain and identify their relations to important pain-related outcomes, particularly in terms of opioid misuse risk and emotion dysregulation among patients with chronic pain receiving treatment in Appalachia. Two hundred and twelve patients presenting to a multidisciplinary pain center completed the Difficulties in Emotion Regulation Scale (DERS-18), Screener and Opioid Assessment for Patients with Pain—Revised (SOAPP-R), and short-form McGill Pain Questionnaire (SF-MPQ). The sensory experience of pain was unrelated to emotion dysregulation (r = 0.06, p=0.57) and weakly related to opioid misuse risk (r = 0.182, p<0.05). In contrast, the affective experience of pain was moderately related to emotion dysregulation (r = 0.217, p<0.05) and strongly related to opioid misuse risk (r = 0.37, p<0.01). In addition, emotion dysregulation predicted variance in opioid misuse risk above and beyond the affective and sensory experiences of pain ((b = 0.693, p<0.001). The results suggest patients with a strong affective experience versus sensory experience of pain and challenges with emotion regulation may require a more comprehensive intervention to address these underlying components in order to reduce their risk of misusing opioid medications.